2022
DOI: 10.1177/10659129221119195
|View full text |Cite
|
Sign up to set email alerts
|

Urban-Rural Differences in Non-Voting Political Behaviors

Abstract: Existing studies on the contemporary U.S. urban-rural divide have neglected its potential role in non-voting political participation. Theoretically, there are mixed expectations: for example, higher social capital in rural areas, alongside a generally older population, suggest rural areas should have greater political participation. Conversely, lower socioeconomic indicators and more physical distance barriers suggest the opposite. Using nationally stratified survey data from the 2018 CCES ( N = 61,000) and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…It is perhaps unsurprising, then, that other research found resources alone do not fully explain why NVP and voting vary. Whether suggesting socioeconomic factors mediate, rather than directly affect, participation (Cohen, Vigoda, and Samorly 2001), resources are slower to change than participation (Miller and Saunders 2016), or that certain factors like location affect the type-but not the rate-of participation (Lin and Trujillo 2022), evidence suggests there is reason to pay greater attention to what elicits participation beyond one's ability to do so (Leighley 1995;Miller and Saunders 2016).…”
Section: Resources Engagement and Emotionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is perhaps unsurprising, then, that other research found resources alone do not fully explain why NVP and voting vary. Whether suggesting socioeconomic factors mediate, rather than directly affect, participation (Cohen, Vigoda, and Samorly 2001), resources are slower to change than participation (Miller and Saunders 2016), or that certain factors like location affect the type-but not the rate-of participation (Lin and Trujillo 2022), evidence suggests there is reason to pay greater attention to what elicits participation beyond one's ability to do so (Leighley 1995;Miller and Saunders 2016).…”
Section: Resources Engagement and Emotionmentioning
confidence: 99%
“…This is especially the case during salient elections: as Rolfe (2016) described, "Higher-intensity campaigns make politics and the upcoming election more salient, not only in increased political discussion among friends, but also in other prominent cues that may indicate to citizens that their friends, neighbors, and coworkers care about the election," (100). Mobilizing people to participate is now even easier given the advent of the Internet and social media, evidenced by studies that suggested online participation is less dependent on resources and location (e.g., Lin and Trujillo 2022), equally as impactful on feelings of efficacy compared to offline participation (Oser, Boulianne, and Halperin 2022), and that it can mediate voter turnout (Settle et al 2016).…”
Section: Recruitment Socialization and Mobilizationmentioning
confidence: 99%
“…Finally, despite our findings here, urban-rural residence may still predict other relevant political attitudes and behaviors. For instance, rurality significantly predicts certain types of political participation (Lin and Lunz Trujillo, 2022). Unfortunately, the present study is limited to the items available in the data set.…”
Section: Resultsmentioning
confidence: 97%
“…The U.S. has an established urban-rural division in numerous aspects of political behavior and public opinion, including vote choice (Johnson and Scala, 2022;Rodden, 2019;Scala and Johnson, 2017), partisanship (Gimpel et al, 2020), anti-establishment candidate support (Cramer, 2016), racial resentment (Nelsen and Petsko, 2021), and willingness to protest or put up a political sign (Lin and Lunz Trujillo, 2022). Furthermore, the urban-rural political division can be found in other countries, such as Canada, the U.K., Denmark, Germany, and more (Armstrong et al, 2022;Ford and Jennings, 2020;Huijsmans, 2022).…”
mentioning
confidence: 99%
“…In the contemporary US, rural areas have increasingly become more conservative and urban areas more liberal, on average (Gimpel et al, 2020;Johnson and Scala, 2020;Mettler and Brown, 2022;Rodden, 2019;Scala and Johnson, 2017). This urban-rural political divide also extends to racial attitudes (Nelsen and Petsko, 2021), populism and anti-intellectualism (Lunz Trujillo, 2022b), immigration attitudes (Fennelly and Federico, 2008), and certain political behaviors (Lin and Lunz Trujillo, 2022). How, then, does the widening urban-rural gap in political affiliation relate to levels of affective partisanship in the US?…”
mentioning
confidence: 99%